Pregnancy outcome in women with bacterial vaginosis - Das, Snehangshu; Basanti, Namoijam; Singh, Ajitkumar; Kulnu, Neiketouzo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Bacterial vaginosis is a condition characterized by alteration in the vaginal flora. It is a common occurrence during pregnancy and is one of the established risk factors for preterm delivery, premature rupture of membranes and chorioamnionitis. The objective of the study was to study the prevalence and effects of bacterial vaginosis during pregnancy. Methods: : The study was a hospital based prospective study conducted in the department of obstetrics and gynaecology, RIMS, Imphal from January to December, 2021. 250 women between 20-28 weeks of gestation underwent examination and testing for bacterial vaginosis and were followed up till delivery. Pregnancy outcomes like pre-term labour, premature rupture of membrane; fetal outcomes like birth-weight, APGAR score, NICU admission, or any other complications were noted. Results: Out of the 250 singleton pregnancies, 48 women (19.2%) were found to have bacterial vaginosis. Pregnancies associated with bacterial vaginosis had more chances of premature rupture of membranes, low birth weight babies. But, there was no significant association of the same to preterm labor and to the rate of NICU admission of the newborns. Conclusions: Vaginal infection during pregnancy should also be entertained seriously and treated well since bacterial vaginosis may directly or indirectly be related to preterm delivery and low birth weight babies.